A collaborative virtual reality environment for liver surgery planning. (October 2021) - Chheang, Vuthea; Saalfeld, Patrick; Joeres, Fabian; Boedecker, Christian; Huber, Tobias; Huettl, Florentine; Lang, Hauke; Preim, Bernhard; Hansen, Christian
Highlights: Immersive VR environment for shared or remote collaboration among surgeons in tumor surgery planning on the example of liver surgery. Virtual resection, resection margins, and real-time risk map visualization are presented. Evaluation from experts reveals insights of potential benefits applicability and limitations. The proposed collaborative VR environment opens a new approach for over-distance collaboration and builds a basis for future medical planning and training. Graphical abstract: Abstract: Surgical planning software is a key component in the treatment of tumor diseases. However, desktop-based systems provide only limited visualization and interaction opportunities. Moreover, collaborative planning among members of a surgical team is only possible to a limited extent. In this work, a collaborative virtual reality (VR) environment to assist liver surgeons in tumor surgery planning is presented. Our aim is to improve virtual resection planning between surgeons in a remote or co-located environment. The system allows surgeons to define and adjust virtual resections on patient-specific organ 3D surfaces and 2D image slices. Changes on both modalities are synchronized, which will enable surgeons to iterate and refine the resection surfaces quickly. In addition, a real-time risk map visualization is presented that displays safety margins around tumors. An evaluation performed by liver surgeons provides information on potential benefits, such as the possibility to visualize complex cases and assessing the safety-critical areas, applicability, and limitations for further improvement.